Europe: an attractive region for Chinese investment - Zreik, Mohamad (Journal of the Belarusian State University. International Relations, 2021)
China’s reform and opening-up policy has led to its economic integration with the community of international partners. China has tended to invest in developing countries rich in natural resources through infrastructure projects and others in exchange for access to natural resources and new markets. This development policy has proven successful due to the large Chinese economic expansion towards many regions and the establishment of economic partnerships. After China’s accession to the World Trade Organization, it opened more to developed countries, especially Europe. China aimed to reach a large and developed international market and to cooperate with the Europeans in order to develop the telecommunications and industry sectors and take advantage of modern European technologies. The strategic importance of this partnership increases with the launch of the Belt and road initiative, as Europe has a geostrategic position along the initiative. This paper discusses the issue of Chinese direct foreign investment toward Europe, analyzes the Sino-European economic cooperation, and points out the motives of both parties to move forward with this partnership.
Keywords: foreign direct investment; Sino-European relations; economic cooperation; Chinese expansion; win-win situation